The acquisition of politeness strategies by Afghan learners of English as a foreign language - Quraishi, Sona (Kansas State University, 2009)
Using the framework for politeness developed by Brown and Levinson (1987), this research evaluates the production of politeness strategies by sophomore and senior EFL learners in Afghanistan by focusing on the language used in letters of inquiry. Twenty eight letters emailed by Afghan students at Balkh University were surveyed by thirteen native American English speakers. Each letter was surveyed by six different American participants who gave their perspectives about the effectiveness and politeness of the language used in the letters by the students. The American participants’ evaluations of politeness were compared with actual linguistic features employed, including the word choice in the salutation and closing, the use of indirect language, and politeness markers (e.g. thank you or other expressions of appreciation). The results show that a relationship between proficiency and politeness exists, consistent with the findings of Tanaka and Kawade (1982) who found that second language learners acquire both linguistic and pragmatic knowledge as the learning of the target language progresses. In addition, this study describes the linguistic behavior perceived as most polite by the native speakers and reflects on possible instructional implications.
Keywords: Politeness; Pragmatics; Effectiveness in communicating ideas; Letters of inquiry; Afghan; English as a foreign language; Language, Linguistics (0290); Language, Modern (0291)